1984
DOI: 10.1149/1.2115779
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth‐Activated Niobates

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a study at RT of the incorporation of Ln 3+ with Na + as a charge compensating species into the Ca 1− x Cd x Nb 2 O 6 solid solution led to considerable host emission, whereas the incorporation of Eu 3+ showed only the characteristic red emission. The cadmium‐rich members were found to be superior in the study 123 . Brittain and Mcallister 131 also investigated luminescence in the Eu 3+ doped (Ca/Cd)Nb 2 O 6 system, with samples excited by an Ar ion laser at 350 nm and 9 K. CdNb 2 O 6 produced a very intense luminescence, with >40 peaks between 526–709 nm, independent of Eu 3+ concentration up to a maximum of 12% substitution, and it was shown that a single Eu 3+ emitting site existed at Cd sites.…”
Section: Other Properties and Applications Of Columbitesmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study at RT of the incorporation of Ln 3+ with Na + as a charge compensating species into the Ca 1− x Cd x Nb 2 O 6 solid solution led to considerable host emission, whereas the incorporation of Eu 3+ showed only the characteristic red emission. The cadmium‐rich members were found to be superior in the study 123 . Brittain and Mcallister 131 also investigated luminescence in the Eu 3+ doped (Ca/Cd)Nb 2 O 6 system, with samples excited by an Ar ion laser at 350 nm and 9 K. CdNb 2 O 6 produced a very intense luminescence, with >40 peaks between 526–709 nm, independent of Eu 3+ concentration up to a maximum of 12% substitution, and it was shown that a single Eu 3+ emitting site existed at Cd sites.…”
Section: Other Properties and Applications Of Columbitesmentioning
confidence: 83%
“…All the phosphors in the solid solution series Ca 1− x Cd x Nb 2 O 6 showed a broad emission band at 470 nm (for excitation at 285 nm). The presence of five cadmium 4 d electrons enables them to participate in the O 2− to Nb 5+ charge transfer, which enhances the luminescence intensity 123 luminescence properties. The PL spectra of self activated pure CdNb 2 O 6 , excited at 272 nm, have a broad and strong blue emission band maximum at 460 nm 124 …”
Section: Other Properties and Applications Of Columbitesmentioning
confidence: 99%
“…5) Among them, CaNb 2 O 6 is known as its interesting luminescence properties arising from electronic transitions between O 2p band and Nb 4d band of the NbO 6 units in the crystal structure. CaNb 2 O 6 itself shows strong blue luminescence upon excitation with ultraviolet (UV) light, 6), 7) and it also works as a host crystal for doping activator ions. 8), 9) In the former self-activated CaNb 2 O 6 , the ordering of the NbO bonding influences strongly the intensity of luminescence.…”
Section: Introductionmentioning
confidence: 99%